Nicaea, the First Capital of the Roman Seljuks (AH 471-490 /1078-1097 AD) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2022)
The study addresses the period in which the Byzantine city of Nicaea became the first capital of the Roman Saljuks at the era of the reign Qutalmish dynasty, the cousin of the Seljuki Sultan Tughril of Anatolia. It was a period full of events, and we do not exaggerate if we say that the control of the Seljuks over Nicaea was the first motivator for the Byzantine Emperor Alexius Comnenus to write to Pope Urban II, who in turn declared the Crusades against the Islamic world.                                                            The study will focus on several axes, including the city location and its religious and strategic importance, the beginnings of the Seljuk presence in Anatolia and the demographic  and religious change that  followed  the Battle  of  Manzikert in favor of the Seljuk Turks, and the position of the Roman Seljuks and its founder Suleiman Ibn Qutalmish from the Byzantine internal conflict and their role in weighting one hand over another to the degree to which  they became  representing the protectors of  the Byzantine  cities, including Nicaea, and  then they declare Nicaea the capital of the Roman Seljuks , and the events  that followed until the Byzantines regained the city with the help of the Crusaders.